(untitled) (Journal of Enam Medical College, 2019)
Non-alcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease worldwide and is becoming the most common indication for liver transplant in the Western world. The disease spectrum varies from steatosis to non-alcoholic steatohepatitis (NASH), advanced fibrosis, cirrhosis and hepatocellular carcinoma. The global prevalence of NAFLD and NASH varies from 24–25% and 1.5–6.45% respectively among general population. Despite the disease burden and adverse outcome of the condition, no highly effective treatment is currently available for NAFLD. Considering its global prevalence and impact clinicians and researchers from different scientific associations worldwide tried hard to develop high-quality international guidelines to improve the management of NAFLD patients in clinical practice. This paper aims to discuss the management options for NAFLD based on five different well-known international guidelines. These guidelines agree on many points and disagree on some points. Notably these guidelines differ in determining alcohol threshold for defining NAFLD, in screening strategies in high-risk patients, the non-invasive test proposed for the diagnosis of NAFLD and advanced fibrosis in patients with NAFLD, in the follow-up protocols and, finally, in the proposed pharmacological treatment strategy. J Enam Med Col 2019; 9(1): 46-56